The complementary oath and its nature (Journal of the College of Basic Education, 2022)
The oath in the language means “power and strength,” and from that is His saying, Glory be to Him: (And if some sayings had been said against us, He would have taken us from Him with an oath) Surah Al-Haqqa verse 44-46. One of the hands is called the oath because it is stronger than the other, and the oath in legal terminology is God Almighty’s testimony of the truthfulness of what the one who swears says or the lack of truthfulness of what the other opponent says.The oath is defined as (a religious and civil act in which the one who swears takes God as a witness to a certain truth or to the fulfillment of what he promised, and he draws His vengeance upon him if he is a liar).